MONOPHYLY AND POLYPHYLY IN THE ORIGIN OF MAMMALS: CURRENT STATE OF THE QUESTION - Tatarinov L.P. (My University, 2002)
The progress in cladistics promoted the revival of the concept of the monophyletic origin of mammals. The discovery of the Early Cretaceous monotreme Steropodon in Australia gave impetus to the development of these ideas. However, the wide diversity of the Late Triassic mammals, which has recently come to light; morphological peculiarity of haramiyids, and, in particular, the data on the independent development in monotremes of the jaw articulation and middle ear of the mammalian type corroborate the concept of the polyphyletic origin of mammals.